2014
DOI: 10.3136/fstr.20.43
|View full text |Cite
|
Sign up to set email alerts
|

The Optimization of Volumetric Displacement Can Uniformize the Temperature Distribution of Heated Ham during a Vacuum Cooling Process

Abstract: Rapidity is the biggest advantage of vacuum cooling in the food industry, especially for cooked meat. However, the largest volumetric displacement does not guarantee the best temperature uniformity because the structure of the food can affect the mechanisms of heat and mass transfer in food during the vacuum cooling process. Because the temperature uniformity is one of the most important factors in the cooling effect, it is necessary to achieve a uniform temperature distribution across the portion of food by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…For instance, Feng and Sun [21] also found that the recommended pressure reduction rate was 30 mbar/min for artificial casing sausages compared with 20 and 40 mbar/min. Song and Liu found that only properly varying the volumetric displacement can result in uniform temperature distribution across the ham section during the vacuum cooling process [14]. In this study, we also found that employing the volumetric displacement of 0.033 s −1 caused a better uniformity than 0.022 s −1 ( < 0.05).…”
Section: Effect Of Volumetric Displacement On the Temperature Distribsupporting
confidence: 63%
See 1 more Smart Citation
“…For instance, Feng and Sun [21] also found that the recommended pressure reduction rate was 30 mbar/min for artificial casing sausages compared with 20 and 40 mbar/min. Song and Liu found that only properly varying the volumetric displacement can result in uniform temperature distribution across the ham section during the vacuum cooling process [14]. In this study, we also found that employing the volumetric displacement of 0.033 s −1 caused a better uniformity than 0.022 s −1 ( < 0.05).…”
Section: Effect Of Volumetric Displacement On the Temperature Distribsupporting
confidence: 63%
“…Consequently, it can enhance the microbial safety of raw products significantly during the cooling process and storage period [10]. Despite using vacuum cooling for more than sixty years to store leafy vegetables in commercial operations, this technique is still not widely used due to its limitations such as more uniform temperature distribution, lower water loss rate, and lower energy conservation [11][12][13][14]. Amongst these three aspects, temperature distribution requires particular attention especially for the leafy vegetables, because marked temperature differences can often be observed between the leaf and the petiole during the vacuum cooling.…”
Section: Introductionmentioning
confidence: 99%
“…The process of bubbles generating from the bottom and then moving to the surface will strengthen the convection and allowed the water and pork to move rather than motionless during the stage of “before boiling” and “slug flows”. The temperature difference also exits between the surface and the centre of the meat (Song & Liu, ; Ozturk et al ., ). The lower temperature of the meat surface will help to the convective within meat.…”
Section: Resultsmentioning
confidence: 99%
“…Vacuum cooling, a rapid cooling process, has huge ability to cool the porous food [1][2][3][4][5]. Its heat and mass transfer is a complicated process, which has been investigated by many researchers [6][7][8][9][10][11][12][13][14][15][16][17]. Jin et al [6][7][8] developed and validated moisture movement model for vacuum cooling of cooked meat.…”
Section: Introductionmentioning
confidence: 99%
“…The temporal trends of total system pressure, product temperature such as surface temperature, center temperature, and mass-average temperature, and the mass of product were predicted. Compared to the theory study, the vacuum cooling has been used for many kinds of food, like ham [17], chicken breast [18,19], beef [20][21][22][23], potato [24], cherry [25], pork [26,27], mussels [28], carrot [29], rose [30,31], purslane [32], lettuce [33], and others [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%